ANTIBACTERIAL ACTIVITY OF Leea indica LEAF EXTRACT AGAINST Escherichia coli ATCC 25922 - Iin Indayani; Ida Bagus Gede Darmayasa; Ni Luh Suriani (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2025)
Background: Leea indica, a large herbaceous plant traditionally used to treat diarrhea, has been studied for its medicinal potential. However, research on the antibacterial activity of its extract against Escherichia coli has not yet been widely reported.Objective: This study aimed to evaluate the antibacterial activity of Leea indica leaf extract against E. coli ATCC 25922 and to identify its phytochemical profile.Methods: Leea indica leaves were extracted using maceration with 96% ethanol as a solvent, followed by evaporation to obtain the crude extract. The antibacterial activity was tested using the well diffusion method at concentrations of 20%, 15%, 10%, and 5%. The inhibition zones were measured to determine antibacterial potency. Qualitative phytochemical screening was also performed to detect the presence of secondary metabolites.Results: The 20% concentration of Leea indica extract produced the largest inhibition zone (27.26 mm), categorized as a very strong antibacterial effect. Phytochemical analysis confirmed the presence of flavonoids, alkaloids, tannins, phenols, steroids, and saponins as secondary metabolites.Conclusions: This study demonstrates that Leea indica leaf extract exhibits strong antibacterial activity against E. coli ATCC 25922 and contains secondary metabolites that may support its traditional use for treating diarrhea.